Strategi persuasif dalam iklan produk l'Oréal Paris - Dewi, Ganisya Tripangestuti; Ismail, Subur; Tri Widyastuti, Wahyu (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2022)
The purpose of this research is to describe the use of persuasive strategies in L'Oréal Paris advertisements. The approach used is qualitative followed by descriptive exposure using content analysis method in identifying the data being studied. This study refers to Gorys Keraf’s and Pachocińska’s theory which is (1) argumentation with facts (l’argument avec des faits), (2) rhetorical questions (la question rhétorique), (3) imperative sentences (la phrase impérative), and (4) exclamative sentences (la phrase exclamative). Data collection techniques used documentation and note-taking & listening techniques and data analysis techniques using Miles and Hubermen techniques which were divided into three parts, namely data reduction, data presentation, and verification/conclusion. The results of this research indicate that there are forty (40) quotes that contain persuasive strategies. There are thirteen (13) advertising data for L’Oréal Paris products. Based on data analysis, all kinds of persuasive strategies were found in L’Oréal Paris advertisements. Arguments with facts (l'argument avec des faits) found seven (7) quotes with 17%, rhetorical questions (la question rhétorique) found five (5) quotes with 12%, imperative sentences (la phrase imperative) found eleven (11) quotes with 28%, and exclamative sentences (la phrase exclamative) found seventeen (17) quotes with 40%which is the dominant strategy found in L’Oréal Paris advertisements.